Review of medical microbiology and immunology - Levinson, Warren (McGraw-Hill Medical, 2010)
"This book is a concise review of the medically important aspects of microbiology and immunology. It covers both the basic and clinical aspects of bacteriology, virology, mycology, parasitology, and immunology. Its two major aims are (1) to assist those who are preparing for the USMLE (National Boards) and (2) to provide students who are currently taking medical microbiology courses with a brief and up-to-date source of information. My goal is to provide the reader with an accurate source of clinically relevant information at a level appropriate for those beginning their medical education"--Provided by publisher.